2014
DOI: 10.1016/j.firesaf.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of intentional fires, social stress and socio-economic determinants: A case study of Malmö, Sweden

Abstract: a b s t r a c tSince the end of the 1990s, the number of fires has increased dramatically in Malmö, a city in the southernmost part of Sweden. Between 1998 and 2009, the increase was 215%, and a large number of the fires were intentional. The aim of this paper is to deepen our understanding of the underlying causes of the spatial and spatio-temporal distribution of intentional fires in Malmö, and to analyse how different living conditions in Malmö sub-areas may determine the frequency of intentional fires. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 30 publications
0
55
0
Order By: Relevance
“…Corcoran et al [12] examined the impact of calendar events (e.g., public and school holidays and major sports events) and found that fire incidents would significantly increase during school holidays. Guldåker and Hallin [13] found that living conditions and socioeconomic stress can greatly affect the spatiotemporal patterns of intentional fires. So far, most of the existing work on urban fires, however, has focused on the cases in developed countries, such as the UK [7,9,11,12], Canada [10], Australia [11] and Sweden [13].…”
Section: Introductionmentioning
confidence: 99%
“…Corcoran et al [12] examined the impact of calendar events (e.g., public and school holidays and major sports events) and found that fire incidents would significantly increase during school holidays. Guldåker and Hallin [13] found that living conditions and socioeconomic stress can greatly affect the spatiotemporal patterns of intentional fires. So far, most of the existing work on urban fires, however, has focused on the cases in developed countries, such as the UK [7,9,11,12], Canada [10], Australia [11] and Sweden [13].…”
Section: Introductionmentioning
confidence: 99%
“…The efforts to prevent fire in the residential areas are influenced by the social conditions of the community and the index living condition (ILC). This was mentioned by Niklas Guldaker [7] for the Malmo Sweden study case. Lopes and Hao [8,9] state that the mitigation of fire is a joint effort between the community and the government as the decision-maker for public policies.…”
Section: Related Workmentioning
confidence: 88%
“…This leads to potential contributions of this study for further research, that is, assisting with (1) hypothesis formulation with respect to the factors associated with urban fires and (2) future fire and rescue management and planning. For instance, it might be of interest to investigate why there is a descending trend of urban fires during 2004-2008, and why the year 2008 had the lowest number of fire events and whether it was affected by aforementioned factors like weather and enhanced monitoring due to big events (e.g., [5][6][7]). Additionally, as pointed by [10], the intensifying and persistent fire hot spots in the city proper, particularly for the dwelling fire, might be related to the concentration of old residential buildings that lack fire safety devices.…”
Section: Discussionmentioning
confidence: 99%